Pelatihan Pengolahan Hasil Perikanan bagi Siswa-Siswi Jurusan Agribisnis Perikanan Air Tawar di SMK Negeri 10 Padang - Wati Wati; Meri Rahmania; Nora Susanti; Desi Areva; Gustia Harini; Krisya Wahyu Kinarsih (Warta Pengabdian Andalas, 2023)
Community service is one of the Tridharma of university lecturers apart from teaching and research. To realize this, Lecturers at the Faculty of Economics and Business, PGRI University, West Sumatra, are carrying out Community Partnership Program (PKM) activities with the theme Fishery Product Processing Training for Students of the Freshwater Fisheries Agribusiness Department at SMK Negeri 10 Padang. This PKM aims to provide skills and knowledge to students regarding the processing of freshwater fisheries products and as a form of integrating PKK subjects and productive freshwater fisheries cultivation in implementing the Merdeka Curriculum. In implementing the independent curriculum, there are many ways or models of learning that can be used in the hope that the quality of learning will increase. One model that can be applied is the integrative learning model. This learning model is inductive, which combines several aspects into one process. Class XII students attended this activity and carried out using the lecture method, practical processing of freshwater fishery products, and questions and answers. After participating in this activity, students are expected to be able to practice for themselves how to process freshwater fish into products that have economic value and a high selling value.